Evaluación de la resistencia a la corrosión de la aleación Ti6AI4V modificadas mediante oxidación térmica - Ortiz Jaraba, Dayron Oscar; Schmalbach Trujillo, John Agustin (Universidad Antonio Nariño, 2021)
In the present work, a study was carried out to determine the corrosion resistance of the anodized and thermally oxidized Ti6Al4V alloy for biomedical applications. To carry out the study, light microscopy (OM), anodizing, thermal oxidation in a furnace, corrosion potentials and potentiodynamic polarization curves were performed. In the anodizing test procedure, constant conditions were detected in the samples, but varying the thermal oxidation temperatures from 520 ° C, 560 ° C and 600 ° C. Initially, the results of the microstructures of the material in the cross sections and longitudinal where the α and β phases are observed which are responsible for the mechanical behaviors, high temperatures, resistance to corrosion and biocompatibility. In terms of corrosion, check the open potential curves where the indicated samples are found to have superior behavior with respect to the metal base and in some samples, superior behavior to the others. This was directly related to thermal oxidation temperatures. Two important results were observed in the potentiodynamic curves, the behavior of the anodic and cathodic branches of the samples tested and the rate of corrosion. The above showed that the sample oxidized at 520 ° C showed a better corrosion behavior and a lower corrosion rate compared to the others. Finally, as a conclusion of the project, the thermally improved oxidized samples were determined, the resistance to corrosion at different temperatures with respect to the metal base, this increases the biocompatibility for biomedical systems or applications.